(untitled) (Research, Society and Development, 2020)
Being native to tropical and subtropical regions, temperature and light play an important role in the initial development of physalis (Physalis peruviana L. 1763), as well as the substrate, another relevant factor. Thus, the objective was to evaluate the germination and the initial development of physalis seedlings in different substrates and temperatures. The experiment was carried out from April to June 2018 in the municipality of Capão do Leão. The experimental design was completely randomized in a 4 x 2 factorial scheme, with the factors, substrates (vermiculite, carbonized rice husks, S10 and coconut fiber) and temperatures (20 ° C and 25 ° C). The emergence rate (IVE) was evaluated daily after sowing and, after 22 days, the percentage of germination, shoot length, shoot number, number of roots, length of the largest root, dry matter weight of the shoot and root, and analysis of the substrates used. For IVE, the highest averages were observed when sowing was carried out on substrate S10 for both temperatures, reaching a value of 4.91 at a temperature of 25º C. Regarding the germination percentage, the highest averages were also observed in substrate S10 at 25 ° C. In the other evaluations there was no interaction between the factors, and when analyzed separately, the highest averages were observed in the substrates S10 and coconut fiber (for length of the aerial part) and at the temperature of 25 ° C. Therefore, the substrate S10 Beifort® and Amafibra® coconut fiber and temperature of 25 ° C, are indicated for the initial development of physalis.